1993
DOI: 10.1038/ki.1993.124
|View full text |Cite
|
Sign up to set email alerts
|

31P NMR spectroscopy investigation of muscle metabolism in hemodialysis patients

Abstract: Calf muscle metabolism of six patients with end-stage chronic renal failure undergoing maintenance hemodialysis and of six control subjects was studied using 31P nuclear magnetic resonance spectroscopy at 4.7 Tesla. Spectra were obtained at rest, during exercise and recovery. At rest, the inorganic phosphate, ATP and phosphocreatine concentrations, and the intracellular pH were similar in both groups of subjects. In the patients, the maximum workload achieved at the end of exercise led to a 84% and 46% depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 21 publications
6
32
0
Order By: Relevance
“…Specific differences among these four studies could not be clearly identified to establish why the cytosolic Pi was comparable to controls; they investigated the same muscles (calf and finger flexors) as the group of studies reporting increased cytosolic Pi, with the exception of the dorsiflexor muscle. 38 Perhaps these findings can be attributed to differences in the techniques used to measure the metabolites at rest, as one study 28 reported using ''unique'' methods of measuring absolute cytosolic Pi. Four studies [40][41][42]45 suggested ''reduced effective muscle mass'' based on the rate of adenosine triphosphate (ATP) synthesis during incremental sub-maximal exercise.…”
Section: Electrophysiological Characteristicsmentioning
confidence: 94%
See 1 more Smart Citation
“…Specific differences among these four studies could not be clearly identified to establish why the cytosolic Pi was comparable to controls; they investigated the same muscles (calf and finger flexors) as the group of studies reporting increased cytosolic Pi, with the exception of the dorsiflexor muscle. 38 Perhaps these findings can be attributed to differences in the techniques used to measure the metabolites at rest, as one study 28 reported using ''unique'' methods of measuring absolute cytosolic Pi. Four studies [40][41][42]45 suggested ''reduced effective muscle mass'' based on the rate of adenosine triphosphate (ATP) synthesis during incremental sub-maximal exercise.…”
Section: Electrophysiological Characteristicsmentioning
confidence: 94%
“…Description of the participants obtained from 10 casecontrol studies [26][27][28][29][30][31][32][33][34][35] provided adequate evidence of equal opportunity of inclusion in the study to demonstrate absence of selection bias. Of the remaining case-control studies, seven 15,[36][37][38][39][40][41] included participants with chronic renal disease not on HD and with comorbidities (clinical evidence of polyneuropathy, varying degrees of paresis, myopathy, renal bone disease, cerebrovascular accident, diabetes mellitus, peripheral vascular disease, etc.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Since evidence of normal mitochondrial oxidative capacity in CRF patients has been reported (11,18), and the companion study showed that O 2 peak is O 2 supply dependent in these rHuEPO treated patients, changes in muscle bioenergetics at maximum exercise after rHuEPO therapy must follow those of maximal O 2 flow from muscle capillary to mitochondria. However, different reports examining muscle cell bioenergetics in these patients provide conflicting results (18)(19)(20)(21)(22). The primary aim of the present study was the analysis of the relationships between muscle O 2 transport and cellular bioenergetics, assessed by 31 P-nuclear magnetic resonance spectroscopy ( 31 P-MRS), before and after erythropoietin therapy.…”
mentioning
confidence: 99%
“…8 Therefore, we propose in this study to follow, by 31 P MRS, the Pi concentration during HD sessions of pigs to test the hypotheses that the intracellular compartment could be the main source of phosphate during HD and that Pi concentrations will decrease during the session, potentially disturbing energy metabolism of the cell and explaining a part of HD intolerance in some patients.…”
mentioning
confidence: 99%